Acremoxanthone E, a Novel Member of Heterodimeric Polyketides with a Bicyclo[3.2.2]nonene Ring, Produced by Acremonium camptosporum W. Gams (Clavicipitaceae) Endophytic Fungus - Meléndez-González, C.; Muria Gonzalez, Jordi; Anaya, A.; Hernández-Bautista, B.; Hernández-Ortega, S.; González, M.; Glenn, A.; Hanlin, R.; Macías-Rubalcava, M. (2015)
Copyright © 2015 Verlag Helvetica Chimica Acta AG, Zürich.Bioactivity-directed fractionation of the organic mycelium extract of the endophytic fungus Acremonium camptosporum W. Gams (Clavicipitaceae), isolated from the leaves of Bursera simaruba (Burseraceae), led to the isolation of six major heterodimeric polyketides, including one not previously characterized acremoxanthone derivative. In addition, the already known acremoxanthone C, acremonidins A and B, and acremoxanthones A and B were obtained. The structure of the new compound was established by extensive NMR studies, including DEPT, COSY, NOESY, HSQC, and HMBC methods. The trivial name proposed for this compound is acremoxanthone E. In addition, the structure of acremoxanthone C was unequivocally established for the first time, through X-ray crystal-structure analysis. The anti-oomycete activities of the pure compounds were tested against four economically important phytopathogenic oomycetes. Inhibitory concentration for 50% diameter growth reduction, IC50, values for the four phytopathogens ranged from 6 to 38 µM. Also, in parallel, the cytotoxic activities against six cancer cell lines were evaluated showing IC50 values similar to those of cisplatin. To the best of our knowledge, this is the first report on three different groups of heterodimeric polyketides, linked by a bicyclo[3.2.2]nonene, such as xanthoquinodins, acremonidins, and acremoxanthones, which are isolated from an endophytic fungus. In addition, a common biosynthetic origin could be proposed.